Composite current collector, secondary battery and electronic device
By designing composite fluids with specific thickness and tensile strength, and cooperating together to enhance the compressive resistance of the negative electrode material layer, the risk of composite fluids breaking during the manufacturing process is solved, and the safety performance and energy density of the secondary battery are improved.
Patent Information
- Application Number
- CN202411976413.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-15
AI Technical Summary
During the manufacturing process, due to the large difference in compaction density between the positive electrode material layer and the negative electrode material layer, the positive electrode material layer is difficult to achieve the expected compaction density. Overvoltage on one side of the negative electrode material layer causes the composite liquid to break, affecting the safety performance and energy density of the secondary battery.
By designing a composite fluid collector, which includes an insulating layer, a first metal layer and a second metal layer, the thickness and tensile strength of the first metal layer, and the rigid parameters of the composite fluid collector are all within a specific range, and the compression resistance of the negative electrode material layer is strengthened, ensuring that when the positive electrode material layer reaches the expected compaction density, the risk of fracture on one side of the negative electrode material layer is reduced, and the thickness of the composite fluid collector is reduced during the cold pressing process, thereby improving the safety performance and energy density of the secondary battery.
It is achieved without damaging the compaction density of the positive electrode material layer, reducing the risk of overvoltage on one side of the negative electrode material layer, improving the safety performance of the secondary battery, and improving the energy density of the secondary battery by reducing the thickness of the composite fluid collection.
Smart Images

Figure CN119833643A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrochemical technology, and in particular to a composite current collector, a secondary battery and an electronic device. Background Art
[0002] Due to their high energy efficiency, secondary batteries are widely used in many fields such as portable electronic devices, electric vehicles, energy storage systems, etc. With the rapid development of related fields, the energy density of secondary batteries needs to be further improved.
[0003] Composite current collectors are favored for their lightweight and beneficial effect on improving the energy density of secondary batteries. However, composite current collectors are limited by the large difference in compaction density of active materials on both sides. Usually, the compaction density of the positive electrode material layer is greater than that of the negative electrode material layer. During the manufacturing process, it is easy for the positive electrode material layer to fail to reach the expected compaction density, and the overpressure on one side of the negative electrode material layer may cause the composite current collector to break, affecting the safety performance of the secondary battery. Summary of the invention
[0004] The purpose of the present application is to provide a composite current collector, a secondary battery and an electronic device to improve safety performance and energy density.
[0005] The first aspect of the present application provides a composite current collector, which includes an insulating layer, a first metal layer, and a second metal layer. The insulating layer is located between the first metal layer and the second metal layer. The thickness of the first metal layer is dA μm and the tensile strength is σAMPa; the thickness of the second metal layer is dBμm and the tensile strength is σB MPa, satisfying: 1≤dA≤8, 80≤σA≤110; the rigidity parameter of the composite current collector is C, C=(dA×σA) / (dB×σB), 0.20≤C≤0.55, optionally, 0.4≤C≤0.5. The composite current collector has the above-mentioned characteristics, and the thickness, tensile strength and rigidity parameters of the first metal layer are within the scope of this application, which helps the positive electrode material layer and the negative electrode material layer to achieve different compaction density requirements, thereby reducing the risk of fracture of the composite current collector due to excessive pressure on one side of the negative electrode material layer while improving the safety performance of the secondary battery. The composite current collector has suitable tensile strength and toughness, and its thickness can be further reduced during the cold pressing process, thereby improving the energy density.
[0006] In one or more embodiments of the present application, dB = dA + x, σB = σA + y, 0 ≤ x ≤ 3, 30 ≤ y ≤ 60. The thickness and tensile strength of the second metal layer in the composite current collector are within the scope of the present application, the first metal layer and the second metal layer cooperate to enhance the compressive strength of one side of the negative electrode material layer, and when the positive electrode material layer reaches the expected compaction density, it is beneficial to reduce the risk of the composite current collector being fractured due to excessive pressure on the positive electrode material layer. At the same time, the thickness of the composite current collector is further reduced during the cold pressing process, further improving the safety performance and volume energy density of the secondary battery.
[0007] In one or more embodiments of the present application, 3≤dA≤5. The thickness of the first metal layer is within the range of the present application, which helps to improve the strength of the composite current collector and further enhance the safety performance of the secondary battery.
[0008] In one or more embodiments of the present application, 3≤dB≤10, 120≤σB≤160. The thickness and tensile strength of the second metal layer are within the scope of the present application, and the compression resistance of the negative electrode material layer is enhanced. When the positive electrode material layer reaches the expected compaction density, it is beneficial to reduce the risk of the composite current collector being broken due to excessive pressure on one side of the negative electrode material layer. At the same time, the thickness of the composite current collector is further reduced during the cold pressing process, further improving the safety performance and volume energy density of the secondary battery.
[0009] In one or more embodiments of the present application, 5≤dB≤8. The thickness of the second metal layer is within the scope of the present application, which enhances the compressive strength of one side of the negative electrode material layer. When the positive electrode material layer reaches the expected compaction density, it is beneficial to reduce the risk of the composite current collector being broken due to excessive pressure on one side of the negative electrode material layer. At the same time, the thickness of the composite current collector is further reduced during the cold pressing process, further improving the safety performance and volume energy density of the secondary battery.
[0010] In one or more embodiments of the present application, the first metal layer includes at least one of aluminum, aluminum alloy, nickel, nickel alloy, titanium or silver; and / or the second metal layer includes at least one of aluminum, aluminum alloy, copper, copper alloy, nickel, nickel alloy, titanium and silver. The material of the first metal layer and / or the second metal layer is within the scope of the present application, and the first metal layer and / or the second metal layer have suitable tensile strength and toughness, which reduces the difference in extension between the positive electrode material layer and the negative electrode material layer on both sides during cold pressing, which is beneficial to reduce the risk of fracture of the composite current collector due to excessive pressure on one side of the negative electrode material layer when the positive electrode material layer reaches the expected compaction density. At the same time, the thickness of the composite current collector is further reduced during the cold pressing process, further improving the safety performance and volume energy density of the secondary battery.
[0011] In one or more embodiments of the present application, the thickness of the insulating layer is dC μm, 1≤dC≤20, and optionally, 2≤dC≤4. The thickness of the insulating layer is regulated within the scope of the present application, and the insulating layer has a suitable thickness, which is beneficial to improving the strength of the composite current collector, while making the composite current collector thinner, further improving the safety performance and volume energy density of the secondary battery.
[0012] In one or more embodiments of the present application, the Young's modulus of the insulating layer is EC GPa, 2≤EC≤5. The Young's modulus of the insulating layer is within the scope of the present application, and the insulating layer has good deformation resistance, which is beneficial to reduce the risk of the composite current collector being broken due to excessive pressure on one side of the negative electrode material layer when the positive electrode material layer is cold pressed, and further improves the safety performance of the secondary battery.
[0013] In one or more embodiments of the present application, the insulating layer includes at least one of the following compounds or derivatives of the following compounds: polyamide, polyimide, polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polycarbonate, polyethylene, polypropylene, polypropylene, acrylonitrile-butadiene-styrene copolymer, polyvinyl alcohol, polystyrene, polyvinyl chloride, polyvinylidene fluoride, polytetrafluoroethylene, sodium polystyrene sulfonate, polyacetylene, silicone rubber, polyformaldehyde, polyphenylene ether, polyphenylene sulfide, polyethylene glycol, polysulfur nitride, polyphenylene, polypyrrole, polyaniline, polythiophene, polypyridine, cellulose, starch, protein, epoxy resin, phenolic resin.
[0014] The second aspect of the present application provides a secondary battery, which includes the composite current collector described in the first aspect of the present application, a positive electrode material layer is arranged on the surface of the first metal layer away from the insulating layer, and a negative electrode material layer is arranged on the surface of the second metal layer away from the insulating layer. The composite current collector has a small mass, which is conducive to improving the energy density of the secondary battery.
[0015] In one or more embodiments of the present application, the negative electrode material layer includes hard carbon. The negative electrode material layer includes hard carbon, and the hard carbon particles have a large hardness, which reduces the probability of being crushed when the negative electrode material layer is over-pressurized, and is conducive to reducing the risk of the composite current collector being broken due to excessive pressure on one side of the negative electrode material layer when the positive electrode material layer reaches the expected compaction density, further improving the safety performance of the secondary battery.
[0016] The third aspect of the present application provides an electronic device, which includes the composite current collector described in the first aspect of the present application or the secondary battery described in the second aspect of the present application. Therefore, the electronic device provided by the present application has good safety performance.
[0017] Beneficial effects of this application:
[0018] The present application provides a composite current collector, which includes an insulating layer, a first metal layer, and a second metal layer, wherein the insulating layer is located between the first metal layer and the second metal layer, wherein the thickness of the first metal layer is dAμm, and the tensile strength is σAMPa; the thickness of the second metal layer is dBμm, and the tensile strength is σB MPa, and the following conditions are satisfied: 1≤dA≤8, 80≤σA≤110; and the rigidity parameter of the composite current collector is C, C=(dA×σA) / (dB×σB), 0.20≤C≤0.55. The composite current collector has the above characteristics, and the thickness, tensile strength and rigidity parameters of the first metal layer and the composite current collector are within the scope of the present application, which helps to achieve different compaction density requirements for the positive electrode material layer and the negative electrode material layer, thereby reducing the risk of the composite current collector being broken due to excessive pressure on one side of the negative electrode material layer under the premise that the positive electrode material layer reaches the expected compaction density, and while improving the safety performance of the secondary battery, the composite current collector has suitable tensile strength and toughness, and the thickness is further reduced during the cold pressing process, thereby improving the energy density.
[0019] Of course, implementing any product or method of the present application does not necessarily require achieving all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application, and a person skilled in the art can also obtain other embodiments based on these drawings.
[0021] Figure 1 Schematic diagram of the cross-sectional structure along the thickness direction of a sodium ion battery obtained by using the composite current collector prepared in Example 1 of the present application.
[0022] Insulating layer 101 ; second metal layer 102 ; first metal layer 103 ; composite current collector 10 ; negative electrode material layer 11 ; positive electrode material layer 21 ; bipolar pole piece 3 ; isolation film 4 . DETAILED DESCRIPTION
[0023] The following will be combined with the embodiments of the present application and the accompanying drawings to clearly and completely describe the technical solutions in the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by those skilled in the art based on the present application belong to the scope of protection of the present application.
[0024] It should be noted that in the specific embodiments of the present application, lithium ion batteries or sodium ion batteries are used as examples of secondary batteries to explain the present application, but the secondary batteries of the present application are not limited to lithium ion batteries and sodium ion batteries.
[0025] The first aspect of the present application provides a composite current collector, which includes an insulating layer, a first metal layer, and a second metal layer. The insulating layer is located between the first metal layer and the second metal layer. The thickness of the first metal layer is dAμm and the tensile strength is σAMPa; the thickness of the second metal layer is dBμm and the tensile strength is σB MPa, 1≤dA≤8, 80≤σA≤110; the rigidity parameter of the composite current collector is C, C=(dA×σA) / (dB×σB), 0.20≤C≤0.55, optionally, 0.4≤C≤0.5. For example, the thickness dA of the first metal layer can be 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, or a range consisting of any two of the values therein; the tensile strength σA of the first metal layer can be 80 MPa, 82 MPa, 85 MPa, 88 MPa, 90 MPa, 92 MPa, 95 MPa, 98 MPa, 100 MPa, 102 MPa, 105 MPa, 108 MPa, 110 MPa, or a range consisting of any two of the values therein; the rigidity parameter C of the composite current collector can be 0.20, 0.30, 0.40, 0.41, 0.42, 0.43, 0.44, 0.45, 0.46, 0.47, 0.48, 0.49, 0.50, 0.51, 0.52, 0.53, 0.54, 0.55, or a range consisting of any two ratios therein. When the rigidity parameter C of the composite current collector is too small, when the positive electrode material layer is in the process of compaction, the tensile strength and toughness of the first metal layer are low, and the composite current collector is easily broken due to excessive pressure. When the rigidity parameter C of the composite current collector is too large, the brittleness is large and it is easy to break during the production process, affecting the process efficiency and reducing production efficiency. Therefore, when the composite current collector has the above characteristics, and the thickness, tensile strength and rigidity parameters of the first metal layer are within the scope of this application, it is helpful for the positive electrode material layer and the negative electrode material layer to meet different compaction density requirements, thereby reducing the risk of the composite current collector being broken due to excessive pressure on one side of the negative electrode material layer under the premise that the positive electrode material layer reaches the expected compaction density. While improving the safety performance of the secondary battery, the composite current collector has suitable tensile strength and toughness, and the thickness is further reduced during the cold pressing process, thereby improving the energy density.
[0026] In one or more embodiments of the present application, dB = dA + x, σB = σA + y, 0 ≤ x ≤ 3, 30 ≤ y ≤ 60. For example, x can be 0, 0.5, 1, 1.5, 2, 2.5, 3, or a range consisting of any two of these values; y can be 30, 35, 40, 45, 50, 55, 60, or a range consisting of any two of these values. The thickness and tensile strength of the second metal layer in the composite current collector are within the scope of the present application. The first metal layer and the second metal layer cooperate to enhance the compressive strength of one side of the negative electrode material layer. When the positive electrode material layer reaches the expected compaction density, it is beneficial to reduce the risk of the composite current collector being fractured due to excessive pressure on the positive electrode material layer. At the same time, the thickness of the composite current collector is further reduced during the cold pressing process, further improving the safety performance and volume energy density of the secondary battery.
[0027] In one or more embodiments of the present application, 3≤dA≤5. For example, dA can be 3, 3.2, 3.5, 3.8, 4, 4.2, 4.5, 4.8, 5, or a range consisting of any two of these values. The thickness of the first metal layer is within the scope of the present application, and the first metal layer has suitable tensile strength and toughness, which helps to improve the strength of the composite current collector and further improve the safety performance of the secondary battery.
[0028] In one or more embodiments of the present application, 3≤dB≤10, 120≤σB≤160. For example, dB can be 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5, 10 or a range consisting of any two of them; σB can be 120, 122, 125, 128, 130, 132, 135, 138, 140, 142, 145, 148, 150, 152, 155, 158, 160 or a range consisting of any two of them. The thickness and tensile strength of the second metal layer are within the scope of the present application, and the compressive strength of one side of the negative electrode material layer is enhanced. When the positive electrode material layer reaches the expected compaction density, it is beneficial to reduce the risk of the composite current collector being broken due to excessive pressure on one side of the negative electrode material layer. At the same time, the thickness of the composite current collector is further reduced during the cold pressing process, further improving the safety performance and volume energy density of the secondary battery.
[0029] In one or more embodiments of the present application, 5≤dB≤8. For example, dB can be 5, 5.2, 5.5, 5.8, 6, 6.2, 6.5, 6.8, 7, 7.2, 7.5, 7.8, 8 or a range consisting of any two of these values. The thickness of the second metal layer is within the scope of the present application, which enhances the compressive strength of one side of the negative electrode material layer. When the positive electrode material layer reaches the expected compaction density, it is beneficial to reduce the risk of the composite current collector being broken due to excessive pressure on one side of the negative electrode material layer. At the same time, the thickness of the composite current collector is further reduced during the cold pressing process, further improving the safety performance and volume energy density of the secondary battery.
[0030] In one or more embodiments of the present application, the first metal layer includes at least one of aluminum, aluminum alloy, nickel, nickel alloy, titanium or silver; and / or the second metal layer includes at least one of aluminum, aluminum alloy, copper, copper alloy, nickel, nickel alloy, titanium and silver. The material of the first metal layer and / or the second metal layer is within the scope of the present application, and the first metal layer and / or the second metal layer have suitable tensile strength and toughness, which reduces the difference in extension between the positive electrode material layer and the negative electrode material layer on both sides during cold pressing, which is beneficial to reduce the risk of fracture of the composite current collector due to excessive pressure on one side of the negative electrode material layer when the positive electrode material layer reaches the expected compaction density. At the same time, the thickness of the composite current collector is further reduced during the cold pressing process, further improving the safety performance and volume energy density of the secondary battery.
[0031] In the present application, in the lithium ion secondary battery, the first metal layer includes at least one of aluminum, aluminum alloy, nickel, nickel alloy, titanium or silver, and the second metal layer includes at least one of copper, copper alloy, nickel, nickel alloy, titanium and silver.
[0032] In the present application, the aluminum alloy may be 1070A, the nickel alloy may be Inconel 600, and the copper alloy may be LBEC-01, LBEC-02, and the like.
[0033] In one or more embodiments of the present application, the thickness of the insulating layer is dC μm, 1≤dC≤20, optionally, 2≤dC≤4. For example, the thickness dC of the insulating layer can be 1 μm, 2 μm, 2.2 μm, 2.5 μm, 2.8 μm, 3 μm, 3.2 μm, 3.5 μm, 3.8 μm, 4 μm, 6 μm, 8 μm, 10 μm, 12 μm, 14 μm, 16 μm, 18 μm, 20 μm or a range consisting of any two of the values. The thickness of the insulating layer is regulated within the scope of the present application, and the insulating layer has a suitable thickness, which is conducive to improving the strength of the composite current collector, while making the thickness of the composite current collector smaller, further improving the safety performance and volume energy density of the secondary battery.
[0034] In one or more embodiments of the present application, the Young's modulus of the insulating layer is EC GPa, 2≤EC≤5. For example, the Young's modulus EC of the insulating layer can be 2Gpa, 2.2Gpa, 2.4Gpa, 2.6Gpa, 2.8Gpa, 3Gpa, 3.2Gpa, 3.4Gpa, 3.6Gpa, 3.8Gpa, 4Gpa, 4.2Gpa, 4.4Gpa, 4.6Gpa, 4.8Gpa, 5Gpa or a range consisting of any two of the values. The Young's modulus of the insulating layer is within the scope of the present application, and the insulating layer has good deformation resistance, which is beneficial to reduce the risk of fracture of the composite current collector due to excessive pressure on one side of the negative electrode material layer when the positive electrode material layer is cold pressed, and further improve the safety performance of the secondary battery.
[0035] In one or more embodiments of the present application, the insulating layer includes at least one of the following compounds or derivatives of the following compounds: polyamide (PA), polyimide (PI), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polyethylene naphthalate (PEN), polycarbonate (PC), polyethylene (PE), polypropylene (PP), polypropylene, acrylonitrile-butadiene-styrene copolymer (ABS), polyvinyl alcohol (PVA), polystyrene (PS), polyvinyl chloride (PVC), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), sodium polystyrene sulfonate (PSS), polyacetylene, silicone rubber, polyoxymethylene (POM), polyphenylene ether (PPO), polyphenylene sulfide (PPS), polyethylene glycol (PEG), polysulfur nitride, polyphenylene, polypyrrole, polyaniline (PANI), polythiophene (PTh), polypyridine, cellulose, starch, protein, epoxy resin (EP), phenolic resin.
[0036] In the present application, there is no particular limitation on the preparation method of the composite current collector, as long as the purpose of the present application can be achieved. For example, the preparation method of the composite current collector can be: using sputtering molding, sputtering the first metal layer and the second metal layer on the two surfaces of the insulating layer to obtain the composite current collector; or using hot pressing molding, setting the first metal layer and the second metal layer on the two surfaces of the insulating layer respectively, and then hot pressing to obtain the composite current collector.
[0037] The present application has no particular limitation on the method for adjusting the thickness dA of the first metal layer, as long as the purpose of the present application can be achieved. For example, the thickness dA of the first metal layer can be adjusted by adjusting the sputtering weight per unit area of the first metal layer.
[0038] In the present application, the tensile strength σA of the first metal layer can be adjusted by regulating the type of the first metal layer, the preparation process and / or the content of each element in the alloy. For example, when the first metal layer is aluminum alloy 1070A, the tensile strength σA of the first metal layer can be adjusted by adjusting the content of each element in the aluminum alloy 1070A; when the first metal layer is aluminum, the tensile strength σA of the first metal layer can be adjusted by adjusting the preparation process of aluminum, and for example, the tensile strength σA of the first metal layer can be adjusted by adjusting the heat treatment process of aluminum.
[0039] The present application has no particular restrictions on the method of adjusting the thickness dB of the second metal layer, as long as the purpose of the present application can be achieved. For example, the thickness dB of the second metal layer can be adjusted by adjusting the sputtering weight per unit area of the second metal layer.
[0040] In the present application, the tensile strength σB of the second metal layer can be adjusted by regulating the type of the second metal layer, the preparation process and / or the content of each element in the alloy. For example, when the second metal layer is aluminum alloy 1070A, the tensile strength σB of the second metal layer can be adjusted by adjusting the content of each element in the aluminum alloy 1070A; when the second metal layer is aluminum, the tensile strength σB of the second metal layer can be adjusted by adjusting the preparation process of aluminum, and for example, the tensile strength σB of the second metal layer can be adjusted by adjusting the heat treatment process of aluminum.
[0041] In the present application, the Young's modulus EC of the insulating layer can be adjusted by regulating the type or degree of polymerization of the insulating layer material.
[0042] In the present application, insulating layers with different thicknesses and Young's moduli can be purchased, and the thickness and Young's modulus of the insulating layer can be obtained by measurement, and the insulating layer with the required thickness and Young's modulus can be selected. The specific test method for the thickness of the insulating layer can refer to the relevant content of the thickness test of the insulating layer in the "Thickness Test" of the "Test Methods and Equipment" section; the specific test method for the Young's modulus of the insulating layer can refer to the content of the "Young's Modulus Test of the Insulating Layer" in the "Test Methods and Equipment" section.
[0043] The second aspect of the present application provides a secondary battery, which includes the composite current collector described in the first aspect of the present application, a positive electrode material layer is arranged on the surface of the first metal layer away from the insulating layer, and a negative electrode material layer is arranged on the surface of the second metal layer away from the insulating layer. The composite current collector has a small mass, which is conducive to improving the volume energy density of the secondary battery.
[0044] In one or more embodiments of the present application, the negative electrode material layer includes hard carbon. The negative electrode material layer includes hard carbon, and the hard carbon particles have a large hardness, which can reduce the probability of being crushed when the negative electrode material layer is over-pressurized, which is beneficial to reduce the risk of one side of the negative electrode material layer being crushed due to excessive pressure when the positive electrode material layer reaches the expected compaction density, and further improve the safety performance of the secondary battery.
[0045] In the present application, the "surface" in the above "a positive electrode material layer is provided on the surface of the first metal layer away from the insulating layer" can be the entire area of the surface of the first metal layer away from the insulating layer, or it can be a partial area of the surface of the first metal layer away from the insulating layer. This application has no special restrictions as long as the purpose of this application can be achieved.
[0046] The positive electrode material layer includes a positive electrode active material. The present application has no particular restrictions on the positive electrode active material as long as the purpose of the present application can be achieved. For example, when the secondary battery is a lithium ion secondary battery, the positive electrode active material may include but is not limited to lithium nickel cobalt manganese oxide (such as NCM811, NCM622, NCM523, NCM111), lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium-rich manganese-based materials, lithium cobalt oxide (LiCoO2), lithium manganese oxide, lithium iron manganese phosphate, and lithium titanate. At least one of the following: when the secondary battery is a sodium ion secondary battery, the positive electrode active material may include but is not limited to sodium iron phosphate, sodium iron pyrophosphate, sodium iron sulfate, Prussian blue (such as Prussian white), sodium nickel iron manganese oxide, and sodium copper iron manganese oxide.
[0047] The positive electrode material layer may also include a positive electrode conductor and a positive electrode binder. The present application does not particularly limit the types of positive electrode conductors and positive electrode binders, as long as the purpose of the present application can be achieved. For example, the positive electrode conductor may include but is not limited to at least one of conductive carbon black (Super P), carbon nanotubes (CNTs), carbon fibers, flake graphite, graphene, metal materials or conductive polymers, and the conductive carbon black may include but is not limited to at least one of acetylene black or Ketjen black. The above-mentioned carbon nanotubes may include but are not limited to single-walled carbon nanotubes and / or multi-walled carbon nanotubes. The above-mentioned carbon fibers may include but are not limited to vapor-grown carbon fibers (VGCF) and / or nano-carbon fibers. The above-mentioned metal materials may include but are not limited to metal powders and / or metal fibers, and specifically, the metal may include but is not limited to at least one of copper, nickel, aluminum or silver. The above-mentioned conductive polymers may include but are not limited to at least one of polyphenylene derivatives, polyaniline, polythiophene, polyacetylene or polypyrrole.
[0048] The present application has no particular limitation on the positive electrode binder as long as the purpose of the present application can be achieved. For example, the positive electrode binder may include but is not limited to at least one of polyacrylic acid, sodium polyacrylate, potassium polyacrylate, lithium polyacrylate, polyimide, polyvinyl alcohol, carboxymethyl cellulose, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, polyimide, polyamide-imide, styrene-butadiene rubber or polyvinylidene fluoride.
[0049] The present application has no particular restriction on the mass ratio of the positive electrode active material, the positive electrode conductive agent, and the positive electrode binder in the positive electrode material layer. Those skilled in the art can select the ratio according to actual needs as long as the purpose of the present application can be achieved.
[0050] The present application has no particular limitation on the thickness of the positive electrode material layer, as long as the purpose of the present application can be achieved. For example, the thickness of the positive electrode material layer is 30 μm to 120 μm.
[0051] Optionally, the positive electrode sheet may further include a positive electrode conductive layer, which is located between the positive electrode current collector and the positive electrode material layer. The composition of the positive electrode conductive layer is not particularly limited, and it can be a conductive layer commonly used in the art. The positive electrode conductive layer includes a positive electrode conductive layer conductive agent and a positive electrode conductive layer binder. The present application has no particular restrictions on the positive electrode conductive layer conductive agent and the positive electrode conductive layer binder, for example, it can be at least one of the above-mentioned positive electrode conductive agent and the above-mentioned positive electrode binder.
[0052] In the present application, the "surface" in the above-mentioned "a negative electrode material layer is provided on the surface of the second metal layer away from the insulating layer" can be the entire area of the surface of the second metal layer away from the insulating layer, or it can be a partial area of the surface of the second metal layer away from the insulating layer. This application has no special restrictions as long as the purpose of this application can be achieved.
[0053] The negative electrode material layer includes a negative electrode active material, which may include but is not limited to natural graphite, artificial graphite, mesophase microcarbon beads, hard carbon, soft carbon, silicon, silicon-carbon composites, Li-Sn alloys, Li-Sn-O alloys, Sn, SnO, SnO2, spinel structured lithiated TiO2-Li4Ti5O 12 Or at least one of Li-Al alloy.
[0054] In some embodiments of the present application, the negative electrode material layer may further include a negative electrode conductive agent and a negative electrode binder. The present application has no particular restrictions on the types of the negative electrode conductive agent and the negative electrode binder, as long as the purpose of the present application can be achieved. For example, it may be at least one of the above-mentioned positive electrode conductive agent and the above-mentioned positive electrode binder. The present application has no particular restrictions on the mass ratio of hard carbon, negative electrode conductive agent, and negative electrode binder in the negative electrode material layer. Those skilled in the art may select according to actual needs, as long as the purpose of the present application can be achieved.
[0055] The present application has no particular limitation on the thickness of the negative electrode material layer, as long as the purpose of the present application can be achieved. For example, the thickness of the negative electrode material layer is 30 μm to 120 μm.
[0056] Optionally, the negative electrode sheet may further include a negative electrode conductive layer, which is located between the negative electrode current collector and the negative electrode material layer. The present application has no particular restrictions on the composition of the negative electrode conductive layer, which may be a conductive layer commonly used in the art. For example, the negative electrode conductive layer includes a negative electrode conductive layer conductive agent and a negative electrode conductive layer binder. The present application has no particular restrictions on the negative electrode conductive layer conductive agent and the negative electrode conductive layer binder, and may be, for example, at least one of the above-mentioned positive electrode conductive agent and the above-mentioned positive electrode binder.
[0057] In the present application, the secondary battery also includes an electrolyte solution including an electrolyte salt and a non-aqueous solvent.
[0058] In the present application, in a lithium-ion secondary battery, the electrolyte salt includes a lithium salt, and the present application has no particular restrictions on the lithium salt, as long as the purpose of the present application can be achieved. For example, the lithium salt may include but is not limited to lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium hexafluoroarsenate (LiAsF6), lithium perchlorate (LiClO4), lithium tetraphenyl boron (LiB(C6H5)4), lithium methanesulfonate (LiCH3SO3), lithium trifluoromethanesulfonate (LiCF3SO3), lithium bis(trifluoromethanesulfonyl)imide (LiN(SO2CF3)2), tris(trifluoromethylsulfonyl)methyl lithium (LiC(SO2CF3)3), lithium hexafluorosilicate (LiSiF6), lithium bis(oxalatoborate) (LiBOB) and lithium difluoroborate (LiF2OB). The present application has no particular restrictions on the content of the lithium salt in the electrolyte, as long as the purpose of the present application can be achieved.
[0059] In the present application, in the sodium ion secondary battery, the electrolyte salt includes a sodium salt, and the present application has no particular restrictions on the sodium salt, as long as the purpose of the present application can be achieved. For example, the sodium salt may include but is not limited to at least one of sodium hexafluorophosphate (NaPF6), sodium tetrafluoroborate, sodium hexafluoroarsenate, sodium bisoxalatoborate, sodium trifluoromethanesulfonate or sodium perchlorate. The present application has no particular restrictions on the content of the sodium salt in the electrolyte, as long as the purpose of the present application can be achieved.
[0060] The present application has no particular limitation on the non-aqueous solvent as long as the purpose of the present application can be achieved. For example, the non-aqueous solvent may include but is not limited to at least one of carbonate compounds, carboxylate compounds, ether compounds or other organic solvents.
[0061] The carbonate compound may include but is not limited to at least one of a linear carbonate compound, a cyclic carbonate compound or a fluorinated carbonate compound. The linear carbonate compound may include but is not limited to at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC) or methyl ethyl carbonate (MEC). The cyclic carbonate may include but is not limited to at least one of ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC) or vinyl ethylene carbonate (VEC). The fluorinated carbonate compound may include, but is not limited to, at least one of fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, or trifluoromethylethylene carbonate. The above-mentioned carboxylate compound may include, but is not limited to, at least one of methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decalactone, valerolactone, or caprolactone. The above-mentioned ether compound may include but is not limited to at least one of dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, 1-ethoxy-1-methoxyethane, 2-methyltetrahydrofuran or tetrahydrofuran. The above-mentioned other organic solvents may include but are not limited to at least one of dimethyl sulfoxide, 1,2-dioxolane, cyclopentane, methyl cyclopentane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate or trioctyl phosphate. The present application has no particular restrictions on the content of the non-aqueous solvent in the electrolyte, as long as the purpose of the present application can be achieved.
[0062] In the present application, the secondary battery also includes a separator. The present application has no particular restrictions on the separator, as long as the purpose of the present application can be achieved. For example, the material of the separator may include but is not limited to polyethylene (PE), polypropylene (PP)-based polyolefins (PO), polyesters (e.g., polyethylene terephthalate (PET) film), cellulose, polyimide (PI), polyamide (PA), spandex or aramid. The type of separator may include at least one of a woven membrane, a non-woven membrane, a microporous membrane, a composite membrane, a rolled membrane or a spun membrane.
[0063] In some embodiments of the present application, the isolation film may include a substrate layer and a surface treatment layer. The substrate layer may be a non-woven fabric or a composite film having a porous structure, and the material of the substrate layer may include at least one of polyethylene, polypropylene, polyethylene terephthalate or polyimide. Optionally, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film may be used.
[0064] Optionally, a surface treatment layer is disposed on at least one surface of the substrate layer. The surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by mixing a polymer and an inorganic layer.
[0065] In some embodiments of the present application, the inorganic layer includes inorganic particles and an inorganic layer binder. The present application has no particular restrictions on inorganic particles, such as inorganic particles can include at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. The present application has no particular restrictions on the inorganic layer binder, such as the inorganic layer binder can be at least one of the above-mentioned positive electrode binders. In some embodiments of the present application, the polymer layer includes a polymer, and the material of the polymer includes at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylate, polyvinyl pyrrolidone, polyvinyl ether or polyvinylidene fluoride or poly (vinylidene fluoride-hexafluoropropylene).
[0066] In the present application, there is no particular limitation on the thickness of the isolation film, as long as the purpose of the present application can be achieved. For example, the thickness of the isolation film may be 3 μm to 30 μm.
[0067] In some embodiments of the present application, the secondary battery includes two bipolar pole pieces and a separator arranged in a stacked manner, the bipolar pole piece includes a composite current collector, the composite current collector includes an insulating layer, a first metal layer, and a second metal layer, the insulating layer is located between the first metal layer and the second metal layer, a positive electrode material layer is arranged on the surface of the first metal layer away from the insulating layer, and a negative electrode material layer is arranged on the surface of the second metal layer away from the insulating layer. Figure 1As shown, the secondary battery includes a bipolar pole piece 3 and a separator 4 stacked, the bipolar pole piece 3 includes a composite current collector 10, the composite current collector 10 includes an insulating layer 101, a second metal layer 102 and a first metal layer 103, a positive electrode material layer 21 is arranged on the surface of the first metal layer 103 away from the insulating layer 101, a negative electrode material layer 11 is arranged on the surface of the second metal layer 102 away from the insulating layer 101, and a separator 4 is arranged between the two bipolar pole pieces 3, and the negative electrode material layer 11 of one bipolar pole piece 3 is arranged opposite to the positive electrode material layer 21 of the other bipolar pole piece 3. In the present application, the composite current collectors may be the same or different; the first metal layer and the second metal layer in the composite current collector may be the same or different.
[0068] The secondary battery also includes a shell for accommodating a bipolar pole piece, a separator, a bipolar pole piece and an electrolyte, as well as other components known in the field of secondary batteries, and this application does not limit the above-mentioned other components. This application does not specifically limit the shell, and it can be a shell known in the art, as long as the purpose of this application can be achieved. For example, the shell can be a hard shell or a flexible shell. The material of the hard shell can be metal, and this application does not limit the type of metal, and a metal hard shell known in the art can be used, as long as the purpose of this application can be achieved. The flexible shell can be a metal plastic film, such as an aluminum plastic film, a steel plastic film, etc.
[0069] The preparation process of the secondary battery of the present application is well known to those skilled in the art, and there is no particular limitation in the present application. For example, the preparation process of the secondary battery may include but is not limited to the following steps: stacking the bipolar pole piece, the separator and the bipolar pole piece in order, and winding, folding and other operations as needed to obtain an electrode assembly of a winding structure, placing the electrode assembly in a shell, injecting the electrolyte into the shell and sealing it to obtain a secondary battery. Alternatively, stacking the bipolar pole piece, the separator and the bipolar pole piece in order, and then fixing the four corners of the entire laminated structure with tape to obtain an electrode assembly of a laminated structure, placing the electrode assembly in a shell, injecting the electrolyte into the shell and sealing it to obtain a secondary battery. In addition, overcurrent protection elements, conductive plates, etc. may also be placed in the shell as needed to prevent the pressure inside the secondary battery from rising and overcharging and discharging.
[0070] The third aspect of the present application provides an electronic device, which includes the composite current collector described in the first aspect of the present application or the secondary battery described in the second aspect of the present application. The present application does not particularly limit the type of electronic device, and it can be used for any electronic device known in the prior art. In some embodiments of the present application, the electronic device may include but is not limited to a laptop computer, a pen-input computer, a mobile computer, an e-book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, a liquid crystal television, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium ion capacitor, etc.
[0071] Example
[0072] The following examples and comparative examples are given to more specifically describe the embodiments of the present application. Various tests and evaluations were performed according to the following methods. In addition, unless otherwise specified, "parts" and "%" are based on mass.
[0073] Test methods and equipment:
[0074] Composite current collector sampling test method:
[0075] Disassemble the sodium ion battery, take out the bipolar pole piece, clean the negative electrode material layer and the positive electrode material layer on the surface of the bipolar pole piece with acetone, dry the composite current collector, and mark the side coated with the positive electrode material layer with "first metal layer" and the side coated with the negative electrode material layer with "second metal layer", wherein the positive electrode material layer and the negative electrode material layer can be characterized by X-ray diffraction (XRD), chemical element titration, and EDS (Energy Dispersive Spectrometer) element analysis;
[0076] EDS elemental analysis characterization: disassemble the sodium ion battery, obtain the bipolar pole piece, transfer it to a dry room with a humidity of less than 2%, obtain a smooth surface through argon ion polishing technology, and perform EDS elemental analysis on the material layers on the two surfaces of the bipolar pole piece. The material layer containing sodium element is the positive electrode material layer, and the other material layer is the negative electrode material layer.
[0077] Tensile strength test:
[0078] The composite current collectors of the embodiment and the comparative example were baked at 200° C. to burn off the insulating layer in the composite current collectors, and the side on the surface coated with the positive electrode material layer was the first metal layer, and the side on the surface coated with the negative electrode material layer was the second metal layer;
[0079] The tensile strength of the first metal layer and the second metal layer are tested by a tensile test, and the steps are as follows:
[0080] 1. Select a sample without wrinkles and mark it. Use a knife to cut the sample, making sure the edge of the sample is flat, without wavy edges, burrs or gaps. The size after cutting is 5×10cm, and record the cross-sectional area S.
[0081] 2. Clamp the sample: After the high-temperature oven temperature of the universal testing machine rises to a specific temperature (e.g. 180°C), clamp the sample between the upper and lower clamps, ensure that the sample remains perpendicular to the clamp plane, and start the clamp to clamp the sample.
[0082] 3. Start the test: Wait for the high temperature oven temperature to rise to the set value and then start timing. After a certain period of time (e.g. 5 minutes), start the universal testing machine to start the test to ensure that the sample temperature is uniform.
[0083] 4. Tensile test: Use an electronic universal testing machine to perform a tensile test, usually at a certain crossbeam displacement speed (e.g. 1.875 mm / min) until the sample breaks.
[0084] 5. Use video extensometer: For thinner samples (such as samples with a thickness of 8μm and below), it is not suitable to use a contact extensometer to measure deformation. Therefore, a video extensometer is used to track the markings on the sample and measure the entire deformation from the elastic region to the plastic region until the sample breaks.
[0085] 6. Data recording: record the tensile force and tensile stroke, as well as the maximum shear force F at break, and use this to calculate the tensile strength = F / S.
[0086] 7. Test conditions: The center distance of the fixed chuck is set as the test gauge length, the test temperature is controlled at 25±2℃, and the vertical moving speed of the moving test rod is 50mm / min.
[0087] Thickness test:
[0088] The composite current collector of the embodiment and the comparative example is plasma cut longitudinally along the thickness direction to obtain a flat cross section, wherein the side on which the positive electrode material layer is coated is the first metal layer, and the side on which the negative electrode material layer is coated is the second metal layer;
[0089] The cross section was characterized using a Philips XL-30 field emission scanning electron microscope (SEM) with a magnification of 500 times. The thickness of the insulating layer, the first metal layer, and the second metal layer were observed and measured under the electron microscope.
[0090] Young's modulus test of insulation layer:
[0091] Young's modulus refers to the ratio of tensile stress per unit area to the corresponding unit strain. Take the composite current collector of the embodiment and the comparative example, use a material testing machine (model: Shimadzu AGX-V2), take a composite current collector with a length of 5 cm, use a tool to peel off the first metal layer and the second metal layer, and perform a tensile test at a stretching speed of 2 mm / min to obtain a curve of tensile stress and strain, and calculate the slope of the straight line part of the curve to obtain the Young's modulus of the insulating layer.
[0092] Volume energy density test:
[0093] At 25±2℃, charge to 4.2V with 0.2C current, then charge to 0.02C with 4.2V constant voltage; let stand for 5min, then discharge to 2.8V with 0.2C constant current, let stand for 5min, monitor the discharge process with a battery tester (Neware CT-4016-5V-100A), and obtain the discharge energy E of the secondary battery in Wh. Use a vernier caliper to test the length L, width W, and thickness D of the secondary battery. V=L×W×D, in mm 3 , volume energy density calculation: VED = E × 10 6 / V, unit is Wh / L. Three secondary battery samples are tested for each embodiment or comparative example, and the average value is taken.
[0094] Example 1
[0095] <Preparation of Composite Current Collector>
[0096] The insulating layer material is selected from PET (weight average molecular weight is 3×10 4 ), the thickness of the insulating layer is 3 μm, and the first metal layer and the second metal layer are arranged on the two surfaces of the insulating layer by hot pressing, and the hot pressing temperature is 100° C. A composite current collector is obtained. The thickness of the first metal layer is 4 μm, and the thickness of the second metal layer is 6 μm.
[0097] <Preparation of bipolar pole piece>
[0098] The positive electrode active materials sodium iron phosphate (NFP), conductive carbon black (Super P), and polyvinylidene fluoride (PVDF) are mixed in a weight ratio of 97.5:1.0:1.5, the conductive carbon black is acetylene black, and N-methylpyrrolidone (NMP) is added as a solvent to prepare a slurry with a solid content of 65wt%, and the positive electrode slurry is obtained after vacuum stirring.
[0099] Hard carbon, conductive carbon black (Super P), and styrene-butadiene rubber (SBR) are mixed in a weight ratio of 97:1.5:1.5, wherein the conductive carbon black is acetylene black. Deionized water is added as a solvent to prepare a slurry with a solid content of 70 wt %. The negative electrode slurry is obtained after vacuum stirring.
[0100] The positive electrode slurry is evenly coated on the surface of the first metal layer of the composite current collector away from the insulating layer and dried at 120°C. The coating weight of the positive electrode material layer after drying is 320 mg / 1540.24 mm 2 After coating, the positive electrode material layer is cold pressed to 2.2g / cm 3 The composite current collector coated with the positive electrode material layer on one side is laid flat on the sample table, and the other side is facing upwards, and the negative electrode slurry is evenly coated on the surface of the second metal layer of the composite current collector away from the insulating layer, and dried at 120°C. After drying, the coating weight of the negative electrode material layer is 138mg / 1540.24mm 2 After coating, the negative electrode material layer is cold pressed to 0.95g / cm 3 The compaction density is then obtained by welding the pole ears to obtain a bipolar pole piece. The width of the positive electrode material layer is 100 mm and the length is 1000 mm, and the width of the negative electrode material layer is 110 mm and the length is 1010 mm.
[0101] <Preparation of Electrolyte>
[0102] In a dry argon atmosphere, ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are first mixed in a mass ratio of EC:EMC:DEC=30:50:20 to obtain a base solvent, and then sodium salt sodium hexafluorophosphate (NaPF6) is added to the base solvent to dissolve and mix evenly to obtain an electrolyte with a sodium salt concentration of 1.15M.
[0103] <Isolation film>
[0104] Polyethylene (PE) with a thickness of 15 μm was selected as the isolation membrane.
[0105] <Preparation of Sodium Ion Batteries>
[0106] The bipolar pole piece, isolation film and bipolar pole piece prepared above are stacked in order, as shown in FIG. Figure 1 As shown, the separator is placed in the middle of the bipolar pole piece to play an isolating role, and the electrode assembly is wound. The electrode assembly is placed in an aluminum-plastic film shell, and the water is removed at 80°C, and the prepared electrolyte is injected. After vacuum packaging, standing, formation (0.02C constant current charging to 3.3V, and then 0.1C constant current charging to 3.6V), degassing, and trimming steps, a sodium ion battery is obtained.
[0107] Example 2 to Example 5
[0108] Except for adjusting the thickness of the first metal layer and the second metal layer according to Table 1, the rest is the same as Example 1.
[0109] Example 6
[0110] Except that the content of each element in the aluminum alloy is adjusted so that the tensile strength of the first metal layer is as shown in Table 1, the rest is the same as Example 1.
[0111] Example 7
[0112] Except that the heat treatment process of the first metal layer aluminum is adjusted so that the tensile strength of the first metal layer is as shown in Table 1, the rest is the same as Example 1.
[0113] Example 8 to Example 11
[0114] Except for adjusting the relevant parameters according to Table 1, the rest is the same as Example 1.
[0115] Example 12
[0116] In addition to adjusting the material of the insulating layer to polyoxymethylene POM (number average molecular weight 3×10 4 ), the rest is the same as Example 1.
[0117] Comparative Example 1 to Comparative Example 3
[0118] Except for adjusting the relevant parameters according to Table 1, the rest is the same as Example 1. In Comparative Example 3, the heat treatment process of the first metal layer aluminum is adjusted to make the tensile strength of the first metal layer as shown in Table 1.
[0119] The preparation parameters and performance parameters of each embodiment and comparative example are shown in Table 1.
[0120]
[0121] The rigidity parameters of the composite current collector, the thickness of the first metal layer, and the tensile strength of the first metal layer will affect the safety performance and volume energy density of the secondary battery. From Examples 1 to 12 and Comparative Examples 1 to 3, it can be seen that when the rigidity parameters of the composite current collector, the thickness of the first metal layer, and the tensile strength of the first metal layer are within the range of this application, the safety performance of the secondary battery is high and the volume energy density is high.
[0122] The thickness of the second metal layer in the composite current collector affects the safety performance and volume energy density of the secondary battery. It can be seen from Examples 1 to 5 that when the thickness of the second metal layer in the composite current collector is within the range of this application, the safety performance of the secondary battery is higher and the volume energy density is higher.
[0123] The type of the first metal layer in the composite current collector affects the safety performance and volume energy density of the secondary battery. It can be seen from Example 1 and Example 6 that when the type of the first metal layer in the composite current collector is within the scope of this application, the safety performance of the secondary battery is higher and the volume energy density is higher.
[0124] The values of x and y will affect the safety performance and volume energy density of the secondary battery. It can be seen from Examples 1 and 5 to 7 that when the values of x and y are within the range of this application, the safety performance of the secondary battery is higher and the volume energy density is higher.
[0125] The thickness of the insulating layer in the composite current collector affects the safety performance and volume energy density of the secondary battery. It can be seen from Examples 1 and 8 to 11 that when the thickness of the insulating layer is within the range of this application, the safety performance of the secondary battery is higher and the volume energy density is higher.
[0126] The type of insulating layer material in the composite current collector affects the safety performance and volume energy density of the secondary battery. It can be seen from Example 1 and Example 12 that when the type of the insulating layer is within the scope of this application, the safety performance of the secondary battery is higher and the volume energy density is higher.
[0127] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0128] Each embodiment in this specification is described in a related manner, and the same or similar parts between the embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.
[0129] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.
Claims
1. A composite current collector, comprising an insulating layer, a first metal layer, and a second metal layer, wherein the insulating layer is located between the first metal layer and the second metal layer, the first metal layer has a thickness of dA μm and a tensile strength of σA MPa; the second metal layer has a thickness of dB μm and a tensile strength of σB MPa, 1≤dA≤8, 80≤σA≤110; The rigidity parameter of the composite current collector is C, C=(dA×σA) / (dB×σB), 0.20≤C≤0.
55.
2. The composite current collector according to claim 1, wherein: 0.4≤C≤0.5。 3. The composite current collector according to claim 1, wherein: dB=dA+x, σB=σA+y, 0≤x≤3, 30≤y≤60.
4. The composite current collector according to claim 1, wherein: 3≤dA≤5.
5. The composite current collector according to claim 1, wherein: 3≤dB≤10,120≤σB≤160.
6. The composite current collector according to claim 5, wherein: 5≤dB≤8.
7. The composite current collector according to any one of claims 1 to 6, wherein: The first metal layer comprises at least one of aluminum, aluminum alloy, nickel, nickel alloy, titanium or silver; and / or, The second metal layer includes at least one of aluminum, aluminum alloy, copper, copper alloy, nickel, nickel alloy, titanium and silver.
8. The composite current collector according to any one of claims 1 to 6, wherein: The thickness of the insulating layer is dC μm, 1≤dC≤20.
9. The composite current collector according to claim 8, wherein: 2≤dC≤4.
10. The composite current collector according to any one of claims 1 to 6, wherein: The Young's modulus of the insulating layer is ECGPa, 2≤EC≤5.
11. The composite current collector according to any one of claims 1 to 6, wherein: The insulating layer includes at least one of the following compounds or derivatives of the following compounds: polyamide, polyimide, polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polycarbonate, polyethylene, polypropylene, polypropylene, acrylonitrile-butadiene-styrene copolymer, polyvinyl alcohol, polystyrene, polyvinyl chloride, polyvinylidene fluoride, polytetrafluoroethylene, sodium polystyrene sulfonate, polyacetylene, silicone rubber, polyformaldehyde, polyphenylene ether, polyphenylene sulfide, polyethylene glycol, polysulfur nitride, polyphenylene, polypyrrole, polyaniline, polythiophene, polypyridine, cellulose, starch, protein, epoxy resin, phenolic resin.
12. A secondary battery comprising the composite current collector according to any one of claims 1 to 11, wherein a positive electrode material layer is disposed on a surface of the first metal layer away from the insulating layer, and a negative electrode material layer is disposed on a surface of the second metal layer away from the insulating layer.
13. The secondary battery according to claim 12, wherein: The negative electrode material layer includes hard carbon. 14 . An electronic device comprising the composite current collector according to claim 1 or the secondary battery according to claim 12 .